Measurement of the tt̄ production cross section in the τ+jets channel in pp collisions at √s = 7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Erö, J.; Fabjan, C.; Friedl, M.; Frühwirth, R.; et al. (My University, 2013)
The top-quark pair production cross section in 7 TeV center-of-mass energy proton-proton collisions is measured using data collected by the CMS detector at the LHC. The measurement uses events with one jet identified as a hadronically decaying τ lepton and at least four additional energetic jets, at least one of which is identified as coming from a b quark. The analyzed data sample corresponds to an integrated luminosity of 3.9 fb-1 recorded by a dedicated multijet plus hadronically decaying τ trigger. A neural network has been developed to separate the top-quark pairs from the W+jets and multijet backgrounds. The measured value of σtt̄= 152 ± 12,(stat.) ± 32,(syst.) ±,(lum.) pb is consistent with the standard model predictions. © 2013 CERN for the benefit of the CMS collaboration.